2020
DOI: 10.1038/s41401-019-0350-5
|View full text |Cite
|
Sign up to set email alerts
|

Tissue-specific relaxin-2 is differentially associated with the presence/size of an arterial aneurysm and the severity of atherosclerotic disease in humans

Abstract: Circulating or tissue-related biomarkers are of clinical value for risk stratification in patients with abdominal aortic aneurysms. Relaxin-2 (RL2) has been linked to the presence and size of arterial aneurysms, and to the extent of atherosclerosis in human subjects. Here, we assessed the expression levels of RL2 in aneurysmal (AA, n = 16) and atherosclerotic (ATH, n = 22) arteries, and established the correlation between RL2 levels and the presence/size of AA and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 89 publications
(93 reference statements)
2
3
0
Order By: Relevance
“…Serum levels of relaxin-2 are higher in the early stages of atherosclerosis and gradually decrease with the progression of the disease, eventually showing comparable results between patients with permanent ischemic manifestations from target organs and healthy subjects ( Table 4 ) [ 134 ]. Supporting these findings, an inverse association of arterial tissue relaxin-2 mRNA levels with the clinical severity of atherosclerotic lesions was recently reported [ 170 ]. Tissue relaxin-2 mRNA levels are inversely correlated with MMP-2 in mild atherosclerosis and positively correlated with eNOS in moderate atherosclerosis, which supports the beneficial effect of relaxin-2 in this pathology [ 170 ].…”
Section: Relaxin-2 As a Biomarker In Cardiovascular Diseasesupporting
confidence: 57%
See 2 more Smart Citations
“…Serum levels of relaxin-2 are higher in the early stages of atherosclerosis and gradually decrease with the progression of the disease, eventually showing comparable results between patients with permanent ischemic manifestations from target organs and healthy subjects ( Table 4 ) [ 134 ]. Supporting these findings, an inverse association of arterial tissue relaxin-2 mRNA levels with the clinical severity of atherosclerotic lesions was recently reported [ 170 ]. Tissue relaxin-2 mRNA levels are inversely correlated with MMP-2 in mild atherosclerosis and positively correlated with eNOS in moderate atherosclerosis, which supports the beneficial effect of relaxin-2 in this pathology [ 170 ].…”
Section: Relaxin-2 As a Biomarker In Cardiovascular Diseasesupporting
confidence: 57%
“…Supporting these findings, an inverse association of arterial tissue relaxin-2 mRNA levels with the clinical severity of atherosclerotic lesions was recently reported [ 170 ]. Tissue relaxin-2 mRNA levels are inversely correlated with MMP-2 in mild atherosclerosis and positively correlated with eNOS in moderate atherosclerosis, which supports the beneficial effect of relaxin-2 in this pathology [ 170 ]. Recently, Klimontov et al (2022) found no associations between serum levels of relaxin-2 and carotid atherosclerosis in patients with type 2 diabetes (T2D) [ 171 ].…”
Section: Relaxin-2 As a Biomarker In Cardiovascular Diseasesupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies revealed decreased serum levels of relaxin in patients with T2D, with inconsistent data on the relationship with glycemic control [ 53 , 54 ]. It was reported that in subjects with CA and PAD, relaxin expression in the arterial walls, as well as serum relaxin levels, is inversely associated with the severity of atherosclerotic lesions [ 55 , 56 ]. Nevertheless, in our patients, we found no association between relaxin and CA.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the relaxin family of hormones upregulates MMP-2 and MMP-9 expression to contribute to vessel remodeling (62,63), suggesting that relaxin-relaxin receptor signaling might be a significant contributor to the sex differences present during AVF maturation as relaxin and its downstream molecules differ between sexes (64)(65)(66)(67)(68). Knockout of the relaxin receptor resulted in decreased outward remodeling in a murine model of AVF failure, accompanied by increased elastin content, reduced elastase activity, increased CD45+ leukocytes, and increased MCP-1 expression (69).…”
Section: Venous Dilationmentioning
confidence: 99%